The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1503/cjs.003713
|View full text |Cite
|
Sign up to set email alerts
|

Spine surgeons’ requirements for imaging at the time of referral: a survey of Canadian spine surgeons

Abstract: Background: Routine imaging of patients with spine-related complaints referred for surgical assessment may represent an inefficient use of technological resources. Our objective was to explore Canadian spine surgeons' requirements with respect to imaging studies accompanying spine-related referrals. Methods:We administered an 8-item survey to all 100 actively practising surgeon members of the Canadian Spine Society that inquired about demographic variables and imaging requirements for patients referred with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…2 A recent survey showed that at least 20% of patients referred to a Canadian surgeon for spinerelated concerns are never seen after having undergone the requisite and costly diagnostic imaging. 3 Of the patients seen, the surgical yield is typically low, with less than 20% requiring a surgical solution. 4,5 In regions where wait times are long, timely clinical triage and prioritization have potential to redirect patients who are inappropriately referred to surgeons and improve access for surgical candidates, making effective use of limited and costly resources.…”
mentioning
confidence: 99%
“…2 A recent survey showed that at least 20% of patients referred to a Canadian surgeon for spinerelated concerns are never seen after having undergone the requisite and costly diagnostic imaging. 3 Of the patients seen, the surgical yield is typically low, with less than 20% requiring a surgical solution. 4,5 In regions where wait times are long, timely clinical triage and prioritization have potential to redirect patients who are inappropriately referred to surgeons and improve access for surgical candidates, making effective use of limited and costly resources.…”
mentioning
confidence: 99%
“…It is common practice for spine surgeons in Canada to require an MRI upon referral. 11,12 Faced with a large number of nonsurgical referrals, this requirement may be an attempt to exclude patients with nonsurgical pathology. 7 It is also quite common for primary care providers to order MRIs for patients with chronic back pain, possibly owing to worsening, persistent or recurrent symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In Canada, the traditional referral process from a primary care provider to a spine surgeon has many regional barriers and inefficiencies. 10,11 The majority of surgeons report wait times from primary care referral to consultation for nonurgent spinal conditions in excess of 6 months despite a substantial proportion closing their practices to new referrals or screening them. 10 Approximately 75%-85% of patients referred to a spine surgeon in Canada are not surgical candidates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in addition to directional exercise and activity modification as suggested by Hall et al , a clinical diagnosis of spinal osteoarthritis for P2 and P4 patients can also allow for more targeted medical management, such as more aggressive use of non-steroidal anti-inflammatory drugs, or more appropriate surgical referrals for patients with P4 without the need for advanced imaging 3064 65 This study has uniquely assessed the Hall system in a broader LBP population that, as noted above, is more representative of the primary care spectrum of chronic LBP. The study by Hall and colleagues evaluated a mixed group of patients assessed in an outpatient rehabilitation setting, suggesting that only patients with insurance coverage or the ability to self-pay were included, and thereby potentially introducing selection bias into the study.…”
Section: Discussionmentioning
confidence: 99%